Relações Públicas na cibercultura: desafios e perspectivas - Barba, Henrique Della [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The rise of the internet as an ambience of interaction between the various social actors brought remarkable transformations to the ambits of language and culture. In this context of reconfigurations, new relations of the social production with the knowledge are observed, putting it like the greatest form of value in the society, at the same time in which the knowledge of the institutions become decentralized from new collective forms of consumption and production of knowledge with the digital media. For organizations, this process has meant opening up for the multidirectional communication environment of the internet, where the public relations activity is important to ensure the symmetrical mediation that connected audiences demand. Through this scenario, this research seeks, from the contributions of the theory of Cyberculture, to narrow the relationship between the synergy of knowledge that the Internet can provide, represented by collective intelligence, with the function of Public Relations in the internal and external environments of organizations aiming at institutional legitimacy

A ascensão da internet como ambiência de interação entre os diversos atores sociais trouxe transformações sem precedentes para as esferas da linguagem e da cultura. Nesse contexto de reconfigurações, observam-se novas relações da produção social com o conhecimento, colocando-o como maior forma de valor na sociedade, ao mesmo tempo em que o saber das instituições é descentralizado a partir de novas formas coletivas de consumo e produção de conhecimento com os meios digitais. Para as organizações este processo significou uma abertura ao ambiente de comunicação multidirecional das redes, em que a atividade Relações Públicas adquire caráter importante para garantir a mediação simétrica que os públicos conectados exigem. Mediante este cenário, esta pesquisa busca, a partir das contribuições da teoria da cibercultura, estreitar a relação entre a sinergia de conhecimentos que a internet consegue proporcionar, representada pela inteligência coletiva, com a função do relações-públicas nos ambientes interno e externo das organizações objetivando a legitimidade institucional
Keywords: Relações publicas; Cibercultura; Comunicação nas organizações; Inteligência coletiva; Cyberculture